Answer:
113/24
Step-by-step explanation:
Simplify the following:
(14 + 1/8)/3
Put 14 + 1/8 over the common denominator 8. 14 + 1/8 = (8×14)/8 + 1/8:
((8×14)/8 + 1/8)/3
8×14 = 112:
(112/8 + 1/8)/3
112/8 + 1/8 = (112 + 1)/8:
((112 + 1)/8)/3
112 + 1 = 113:
(113/8)/3
113/8×1/3 = 113/(8×3):
113/(8×3)
8×3 = 24:
Answer: 113/24
5x + y = 9....multiply by 7
10x - 7y = -18
----------------
35x + 7y = 63 (result of multiplying by 7)
10x - 7y = -18
----------------add
45x = 45
x = 45/45
x = 1
5x + y = 9
5(1) + y = 9
5 + y = 9
y = 9 - 5
y = 4
solution is : (1,4)
=========================
-4x + 9y = 9
x - 3y = -6 ....multiply by 4
----------------
-4x + 9y = 9
4x - 12y = -24 (result of multiplying by 4)
---------------add
- 3y = - 15
y = -15/-3
y = 5
x - 3y = -6
x - 3(5) = -6
x - 15 = -6
x = -6 + 15
x = 9
solution is : (9,5)
Answer:
y=-4x-8
Step-by-step explanation:
use the equation y-y1=m(x-x1) and solve for y
Answer: the answer is 8.8
Step-by-step explanation: multiply 2.2 by 4
2.2 X 4